Measuring Adolescent Self-Awareness and Accuracy Using a Performance-Based Assessment and Parental Report - Zlotnik, Sharon; Toglia, Joan (Frontiers in Public Health, 2018)
Aim The aim of this study was to assess awareness of performance and performance accuracy for a task that requires executive functions (EF), among healthy adolescents and to compare their performance to their parent’s ratings. Method Participants: 109 healthy adolescents (mean age 15.2 ± 1.86 years) completed the Weekly Calendar Planning Activity (WCPA). The discrepancy between self-estimated and actual performance was used to measure the level of awareness. The participants were divided into high and low accuracy groups according to the WCPA accuracy median score. The participants were also divided into high and low awareness groups. A comparison was conducted between groups using WCPA performance and parent ratings on the Behavior Rating Inventory of Executive Function (BRIEF). Results Higher awareness was associated with better EF performance. Participants with high accuracy scores were more likely to show high awareness of performance as compared to participants with low accuracy scores. The high accuracy group had better parental ratings of EF, higher efficiency, followed more rules, and were more aware of their WCPA performance. Conclusion Our results highlight the important contribution that self-awareness of performance may have on the individual’s function. Assessing the level of awareness and providing metacognitive training techniques for those adolescents who are less aware, could support their performance.